Co-Occlusion and Persistence of a Baculovirus Mutant Lacking the Polyhedrin Gene - Hamblin, Martha (1990)
A co-occlusion process was evaluated as a commercially and ecologically acceptable strategy for the development of genetically improved baculovirus insecticides. Coinfection of Spodoptera frugiperda (IPLB-SF-21) tissue culture cells with Autographa californica nuclear polyhedrosis virus (AcMNPV) and an AcMNPV mutant (Ac-E10) lacking the polyhedrin gene resulted in occlusion of both virus types within polyhedra. The amount of occluded Ac-E10 virions in progeny polyhedra populations during serial passage in Trichoplusia ni larvae was evaluated. Maintenance of the mutant in progeny polyhedra required polyhedra inocula containing equal numbers of the two virus types at a high dose. A significant reduction in occluded mutant nucleocapsids occurs with inoculum levels below a 100% lethal dose. At inoculum levels below a 30% lethal dose, the majority of fourth-instar larvae were infected with only one type of virus. The commercial application and ecological advantages of the co-occlusion process are discussed.